Analysis of the "Golden Rule" - a commercial pattern construction method developed in West Germany - Diosana, Franzia Zamudio
To answer the persistent problem of consumer dissatisfaction with the fit of their ready to wear apparel, the Lutterloh System International of West Germany introduced in 1992, the "Golden Rule". It is a pattern making method that the developers claim to make custom-fit patterns in minutes. The "Golden Rule" is a kit consisting of a pattern book and the sizing scale. The sizing scale is a strip of paper to be attached to one end of a regular tape measure. It has two sets numbers ranging from 50-140 cm that represent the bust and hip measurements respectively. The pattern book contains 534 dress styles and combinations with their corresponding patterns in miniature sizes. Each pattern is crossmarked and surrounded by guidelines with numbers alongside them. These numbers are necessary for the manipulation and grading of pattern to a desired size.Once the burst and hip measurements are determined, the scale is pinned on the cross mark and the tape measure brought to the guidelines and stretched up the number stated in the miniature pattern. This is done all throughout then the dots are connected and there a pattern is made. In this research the experimental method was used. The bust and hip measurements of six female subjects each with different body proportions were taken. The subjects ages 20-25 years old was chosen from the pattern book. Using the six measurement combinations from the subjects, patterns were made into actual garments and worn by the subjects for evaluation of fit. Results showed that the fit was satisfactory bu needs some alterations to be perfect. Surplus fullness were observed at the bust mound and the side hip of garments although the darts and seam lines were seen in correct locations. The result of the comparative pattern measurements showed that the "Golden Rule" revolves around the pattern grading methods and principles. The differences in lengths and widths of one pattern size to another represent the grading measurement used in increasing or decreasing the pattern size. The sizes in the sizing scale corresponds to the grading required.